Click chemistry-induced modification of acrylated cellulose nanocrystals for application in PVA-based nanocomposites. (1st December 2022) - Fan, Jing; Fan, Xinyan; Guo, Yunfeng; Wang, Yonggui; Xiao, Zefang; Wang, Haigang; Liang, Daxin; Xie, Yanjun
Abstract: The surface functionalization of cellulose nanocrystals (CNC) is crucial for promoting their diverse applications, especially regarding their use as sustainable biobased polymer reinforcements. In this study, we develop poly (vinyl alcohol) (PVA)–CNC composites with improved tensile strength and gas-barrier performance using CNC-based nanofillers. Acrylated CNCs (ACNCs) were prepared from cellulose via one-pot acid hydrolysis/Fischer esterification; subsequently, surface modification was performed through a thiol–ene reaction to obtain surface-thiolated ACNCs, namely, DACNC, MACNC, and PACNC. The various functional groups on the surface-thiolated ACNCs not only affect the dispersion stability but also alter their interfacial interactions with the PVA matrix, thus realizing the PVA nanocomposites with tailored properties, including the thermal properties, mechanical properties, and gas barrier performance. This study demonstrates that surface-thiolated ACNCs with appropriate surface chemistry and loading levels can serve as excellent nanofillers for PVA, forming biobased composites with desired properties. Graphical abstract: Unlabelled Image